Interplay between human microglia and neural stem/progenitor cells in an allogeneic co‐culture model. Issue 11 (12th September 2013) - Liu, Jia; Hjorth, Erik; Zhu, Mingqin; Calzarossa, Cinzia; Samuelsson, Eva‐Britt; Schultzberg, Marianne; Åkesson, Elisabet
Abstract Experimental neural cell therapies, including donor neural stem/progenitor cells (NPCs) have been reported to offer beneficial effects on the recovery after an injury and to counteract inflammatory and degenerative processes in the central nervous system (CNS). The interplay between donor neural cells and the host CNS still to a large degree remains unclear, in particular in human allogeneic conditions. Here, we focused our studies on the interaction of human NPCs and microglia utilizing a co‐culture model. In co‐cultures, both NPCs and microglia showed increased survival and proliferation compared with mono‐cultures. In the presence of microglia, a larger subpopulation of NPCs expressed the progenitor cell marker nestin, whereas a smaller group of NPCs expressed the neural markers polysialylated neural cell adhesion molecule, A2B5 and glial fibrillary acidic protein compared with NPC mono‐cultures. Microglia thus hindered differentiation of NPCs. The presence of human NPCs increased microglial phagocytosis of latex beads. Furthermore, we observed that the expression of CD200 molecules on NPCs and the CD200 receptor protein on microglia was enhanced in co‐cultures, whereas the release of transforming growth factor‐β was increased suggesting anti‐inflammatory features of the co‐cultures. To conclude, the interplay between human allogeneic NPCs and microglia, significantly affected their respective proliferation and phenotype. Neural cell therapy including human donor NPCs may in addition to offering cell replacement, modulate host microglial phenotypes and functions to benefit neuroprotection and repair.